(untitled) (Research, Society and Development, 2023)
Educational technologies aimed at health education are important tools to encourage self-care. The aim of this study was to develop an educational booklet with guidelines for cancer patients, family members and/or caregivers on the rational use of drugs to control cancer pain. It was initially an integrative review research developed in two stages: bibliographic survey and construction of the booklet. To survey the articles in the literature, a search was carried out in the PubMed®, Bireme (Virtual Health Library) and SciELO (Scientific Electronic Library Online) databases. The booklet was entitled: “Guidance on the use of drugs in the treatment of cancer pain”. It explains the main guidelines regarding the use of pain medication. Faced with the various forms of guidance, pharmaceutical care in promoting the rational use of medicines, helps in a quality based on the principles of sus with easy-to-understand guidelines, giving the patient clarification on the drugs in use. This educational booklet will be able to help in the process of rational use of the medication in cancer patients, being another resource in the dissemination of guidelines, contributing to the self-care of these patients.